Impact of Helicobacter pylori on the gastric microbiome in patients with chronic gastritis: a systematic review and meta-analysis protocol - Aiming Yang; Xinyu Zhao; Ruoyu Ji; Xinyuan Cao; Yizhen Zhang; Yingyun Yang; Weiyang Zheng (BMJ Open, 2023)
Introduction Chronic gastritis is a common disease worldwide. Studies have consistently shown that chronic gastritis is usually associated with gastric microbial dysbiosis, especially the infection of Helicobacter pylori. However, the interaction between H. pylori and non-H. pylori bacteria in patients with chronic gastritis has not been clearly identified yet. Consequently, we designed a protocol for a systematic review and meta-analysis, which focused on identifying the changes in gastrointestinal microbiota composition between patients with H. pylori-infective and non-infective chronic gastritis.Method and analysis We will search PubMed, EMBASE and Cochrane Library databases to retrieve observational studies on humans. The eligible studies must include data about the relative abundance of the gastrointestinal microbiome in patients with H. pylori-infective or non-infective chronic gastritis. Only the data of adults aged over 18 years will be analysed. Two researchers will extract the data independently, and Newcastle–Ottawa Scale will be used to assess the risk of bias. Random-effects model will be performed in quantitative analyses. Correlation analysis, bioinformatics analysis and function analysis will be performed.Discussion Currently, numerous studies have revealed the role of H. pylori in chronic gastritis. However, the alterations of non-H. pylori bacteria in patients with chronic gastritis remain an open question. The results of our study might provide new insights into future diagnosis and treatments.Ethics and dissemination This study is based on published documents, unrelated to personal data, so ethical approval is not in need. The results of this study are expected to be published in journals or conference proceedings.PROSPERO registration number CRD42020205260; Pre-results.